8 - The Role of ICT in Curtailing Electoral Fraud and Violence in Nigeria: A Study of the 2019 General Election in Lagos State - Chukwuma, Ifeanyi .U. (Africa Development, 2022)
Elections can be described as the hallmark of democracy and integral for a democratic society to remain stable. However, electoral process in Nigeria has been marred with fraud and violence. Electoral violence and fraud remain a major threat to the stability of democracy in Nigeria. To reduce the occurrence of violence and fraud, INEC introduced the Smart Card Reader (SCR) which was used to verify the authenticity of the Permanent Voters Card (PVC). The use of ICT during the 2019 elections limited the extent to which political actors can intimidate or harass INEC officials to commit electoral fraud, it also reduced the number of electoral petitions and in Lagos State, there was a reduction in violence experienced during the elections.